Preoperative SARS-CoV-2 Infection Screening before Thoracic Surgery during COVID-19 Pandemic: A Multicenter Retrospective Study - Silvia Fiorelli; Cecilia Menna; Federico Piccioni; Gabriele Zuanetti; Franco Valenza; Marco Rispoli; Dario Amore; Monica Rocco; Erino Angelo Rendina; Mohsen Ibrahim; Domenico Massullo (International Journal of Clinical Practice)
Objectives. During coronavirus disease (COVID-19) pandemic, preoperative screening before thoracic surgery is paramount in order to protect patients and staff from undetected infections. This study aimed to determine which preoperative COVID-19 screening tool was the most effective strategy before thoracic surgery. Methods. This retrospective cohort multicenter study was performed at 3 Italian thoracic surgery centers. All adult patients scheduled for thoracic surgery procedures from 4th March until 24th April, 2020, and submitted to COVID-19 preoperative screenings were included. The primary outcome was the yield of screening of the different strategies. Results. A total of 430 screenings were performed on 275 patients; 275 anamnestic questionnaires were administered. 77 patients were screened by an anamnestic questionnaire and reverse transcriptase polymerase chain reaction (RT-PCR). 78 patients were selected to combine screening with anamnestic questionnaire and chest computed tomography (CT). The positive yield of screening using a combination of anamnestic questionnaire and RT-PCR was 7.8% (95% CI: 2.6–14.3), while using a combination of anamnestic questionnaire and chest CT was 3.8% (95% CI: 0–9). Individual yields were 1.1% (95% CI: 0–2.5) for anamnestic questionnaire, 5.2% (95% CI: 1.3–11.7) for RT-PCR, and 3.8% (95% CI: 0–9). Conclusions. The association of anamnestic questionnaire and RT-PCR is able to detect around 8 positives in 100 asymptomatic patients. This combined strategy could be a valuable preoperative SARS-CoV-2 screening tool before thoracic surgery.